The corporate influence on food charity and aid: The “Hunger Industrial Complex” and the death of welfare - Caraher, Martin; Furey, Sinéad (Frontiers in Public Health, 2022)
There is an existing literature on how food companies, including the unhealthy food commodity industries, influence policy through a number of approaches. Direct approaches include lobbying and funding of research. Backdoor or indirect tactics used by food companies to demonstrate engagement include funding community groups, tactics previously used by the tobacco industry. Food industry support for food charities engaged in food donations is an area that has not received attention. This is another backdoor approach and one which may compromise more general public health policy. It is no surprise that the companies that engage in this can be largely fall under the rubric of unhealthy food commodity industries. This link is sometimes referred to as the “hunger industrial complex” and is based on the argument that an alliance exists between the food industry and the food banking movement. With rising levels of food insecurity there is pressure on the food system to donate food to charitable enterprises such as food banks and soups kitchens, which is often encouraged by government policy such as “Good Samaritan legislation”. Food businesses contribute surplus food and often promote it as part of their corporate social responsibility agenda. The argument presented here is not an anti-food charity one but one which challenges the development of charitable food aid as a system and a replacement for public policy. The reasons for this can be summarized under three headings: (1) such donation systems compromise the wider application of public food welfare and give the impression that food poverty is being addressed; (2) the links with food corporations provide a backdoor for influence on wider food policies; and (3) researchers taking money from food charities may be compromised by the direct and indirect relationships with companies. The focus in this paper is on the latter two issues; the first will be established as a context with work we have published elsewhere. This article draws on examples from the UK of how charities have linked with chocolate and soft drink companies. Examples include: “For every Easter egg bought on the Cadbury Worldwide Hide, Cadbury will donate an Easter egg to a food bank in our network”; a Coca-Cola initiative in December 2021 “Win a meal, give a meal on-pack competition across Coca-Cola Original Taste and Coca-Cola Zero Sugar consumption packs, giving consumers the chance to win food-related vouchers, while donating to FareShare”; and an October 2021 initiative where “McDonald's joins forces with FareShare to fund 1 million meals for UK families”. These relationships go beyond companies donating surplus food to food charities such as food banks and pantries to encouraging consumers to buy their products with the promise that the company will contribute products to such charities or provide cash donations in return for the purchase of their product.